Learning to Teach Argumentation: Research and development in the science classroom - Simon, Shirley; Erduran, Sibel; Osborne, Jonathan (International journal of science education, 2006)
The research reported in this study focuses on an investigation into the teaching of argumentation in secondary science classrooms. Over a 1-year period, a group of 12 teachers from schools in the greater London area attended a series of workshops to develop materials and strategies to support the teaching of argumentation in scientific contexts. Data were collected at the beginning and end of the year by audio-recording and video-recording lessons where the teachers attempted to implement argumentation. To assess the quality of argumentation, analytical tools derived from Toulmin's argument pattern were developed and applied to classroom transcripts. Teachers' use of argumentation developed across the year, the pattern of use was teacher-specific, as was the nature of change. To inform future professional development programmes, transcripts of five teachers, three showing a significant change and two showing no change, were analysed in more detail to identify features of teachers' oral contributions that facilitated and supported argumentation. All teachers attempted to encourage a variety of processes involved in argumentation; teachers whose lessons included the highest quality of argumentation (Toulmin's argument pattern analysis) also encouraged higher-order processes in their teaching. The analysis of teachers' facilitation of argumentation has helped to guide the development of in-service materials and to identify the barriers to learning in the professional development of less experienced teachers.